PENGARUH BIAYA PROMOSI TERHADAP VOLUME PENJUALAN BATIK SASIRANGAN BORDIR (STUDI KASUS PADA BUNGA BANGKAL SASIRANGAN) - periyadi -; Amalia Wahyuni (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
Abstract, The main objective in this research is to review and analyze (1) How much influence the cost of promotion on the sales volume of Bangkal Sasirangan Bunga products. The targets in this study include (1) Increasing the sales volume of Batik Sasirangan Bordir through promotion in accordance with the cost or budget that is owned. (2) Making guidelines for craftsmen or home industry players of Batik Sasirangan Bordir to increase sales volume. This research is a qualitative descriptive study, which will try to find out the relationship between the cost of promotion with the sales volume of Sasirangan Embroidery Batik "Bunga Bangkal Sasirangan". Regression analysis is a statistical method that aims to see the direction of the relationship and the magnitude of influence between 2 or more variables in a linear form. Based on the results of R Square in the first regression = 0.198, it means that the magnitude of the ability of variable X namely the Cost of Promotion in explaining the volume of Batik Sasasangan border sales "Bunga Bangkal Sasirangan" by 19.8%, while for 80.2% the level of sales volume of Batik Sasasangan border "Bunga Bangkal Sasirangan" is explained by other variables outside the X variable. Sales volume of Bangkal Sasirangan Flower Products also often changes. Changes in sales volume are influenced by several factors, namely: Internal factors, which affect the sales volume of Bangkal Sasirangan Flowers, namely sales activities, distribution activities, promotional activities, quality or fashion, and determining the selling price of products. External factors that affect the volume of sales of Bangkal Sasirangan Flowers, for example, the purchasing power of consumers and people's tastes.